Identification of selective inhibitors of sphingosine kinases 1 and 2 through a structure–activity relationship study of 4-epi-jaspine B. Issue 12 (15th June 2017) - Ohno, Hiroaki; Honda, Maho; Hamada, Naoka; Miyagaki, Jun; Iwata, Akira; Otsuki, Kazuhiro; Maruyama, Toru; Nakamura, Shinya; Nakanishi, Isao; Inuki, Shinsuke; Fujii, Nobutaka; Oishi, Shinya
Graphical abstract: Abstract: We recently reported that 4- epi -jaspine B exhibits potent inhibitory activity towards sphingosine kinases (SphKs). In this study, we investigated the effects of modifying the 2-alkyl group, as well as the functional groups on the THF ring of 4- epi -jaspine B using a diversity-oriented synthesis approach based on a late-stage cross metathesis reaction. The introduction of a p -phenylene tether to the alkyl group was favored in most cases, whereas the replacement of a carbon atom with an oxygen atom led to a decrease in the inhibitory activity. Furthermore, the introduction of a bulky alkyl group at the terminus led to a slight increase in the inhibitory activity of this series towards SphKs compared with 4- epi -jaspine B (the Q values of compound13 for SphK1 and SphK2 were 0.2 and 0.4, respectively). Based on this study, we identified two isoform selective inhibitors, including the m -phenylene derivative4 [IC50 (SphK1) ≥30 μM; IC50 (SphK2) = 2.2 μM] and the methyl ether derivative22 [IC50 (SphK1) = 4.0 μM; IC50 (SphK2) ≥30 μM].